BENCHMARKING AND CONFIGURATION OF OPEN-SOURCE MANUFACTURING EXECUTION SYSTEM (MES) APPLICATION - Laksmana, Ganesha Nur; Tanaya, Prianggada Indra; Indrayadi, Yuki (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Information now is an important element to every growing industry in the world. In order to keep up with other competitors, endless improvements in optimizing overall efficiency are needed. There still exist barriers that separate departments in PT XYZ and caused limitation to the information sharing in the system. Open-Source Manufacturing Execution System (MES) presents as an IT based application that offers wide variety of customization to eliminate stovepipes by sharing information between departments. Benchmarking is used to choose the best Open-Source MES Application, and Dynamic System Development Method (DSDM) is adopted as this work guideline. As a result, recommendations of the chosen Open-Source MES Application are represented.